Traditional leaders and new local government dispensation in South Africa - (:unkn) unknown (My University, 2002)
Approximately three quarters of population in South Africa live in rural areas and they are under the governance of traditional leadership, whose practice has been the source for controversy recently. The institution of traditional leadership has been regarded as the main ruling system closest and accepted by the people at the grassroots level. Local government in South Africa is presently in a process of fundamental transformation. One of the major problems South Africa inherited from apartheid was a structure of race based municipal boundaries. Demarcation is one of the controversial factors dogging the period of local government history. Demarcation was necessary to remove all traces of apartheid borders and to allow for more democratic municipal government.
Keywords: African Research